Pregnant women's experiences of extreme exposure to bushfire associated smoke: a qualitative study - Deborah Davis; Katelyn Barnes; Rebecca Williamson; Alison M Behie; Christine Phillips; Rosalie Aroni; Celia Roberts; Ella Kurz; Danielle Schoenaker; Christopher J Nolan (IOP Publishing, 2023)
In 2019/2020, multiple bushfires burned across south-east Australia converging into unprecedented megafires that burned 5.8 million hectares. From October 2019-February 2020, 80% of Australians were affected by smoke from these fires, exposing them to dramatic increases of PM _2.5 in the air at an average level of ∼70 μ g m3 per day, well above the World Health Organisation recommendation of ∼10 μ g m3. Maternal exposure to PM _2.5 has been associated with negative birth outcomes and an increased rate of birth defects, yet there is a dearth of literature regarding how pregnant women deal with exposure to bushfire smoke. The aim of this study was thus to investigate how pregnant and postpartum women experienced severe bushfire smoke associated with the 2019-2020 bushfires in south-east Australia and the strategies they used to mitigate exposure to smoke for themselves and their unborn or newborn children. Forty-three women who were exposed to fire and/or smoke from the 2019-2020 bushfires participated in one-on-one semi-structured interviews via phone or videoconference. These women were selected purposively from a larger group of women who had elected to be interviewed. After interview, data were transcribed and thematically analysed using the four phases of disaster response (prevention, preparedness, response, recovery) as a frame. Overall, our results indicated that public health advice failed to meet the unique needs of this group. While many protected their properties appropriately and were reasonably well prepared for evacuation, they were unprepared for the disruption to vital services including power and communications. Women exposed to smoke inundation were unprepared for this outcome and self-initiated a variety of strategies. The support of community was also key to recovery. There is a clear need for specific recognition of the needs of pregnant women across all phases of disaster response, incorporating public health messaging, peer support, and access to resources.